Calcium and the release of atrial natriuretic peptide : a study of calcium-binding proteins interacting with atrial specific granules - Doubell, A. F. (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1993.